How to embrace interdisciplinarity in sport science - An approach at the ÖSG Congress Innsbruck 2024 - Linda Rausch; Johannes Burtscher; Gerhard Ruedl; Kurt Schindelwig; Lisa Steidl-Müller; Maurice Mohr (Bern Open Publishing, 2024)
Introduction The 19th Congress of the Austrian Sport Science Society ("Österreichische Sportwissenschaftliche Gesellschaft, ÖSG"), held in Innsbruck, Austria, centered on the theme of" Embracing Interdisciplinarity in Sport Science." The idea of interdisciplinarity in sport science has been discussed for over three decades and stems from its position as a cross-sectional discipline integrating various natural and social sciences such as training science, sports medicine, biomechanics, sport pedagogy, sport psychology, sport sociology, and sport history. More recently, sports economy and sports management have also emerged as significant areas within sport science. Sports science is characterized by its strong practical relevance. It often focuses on applied research, where interdisciplinarity plays a critical role. Interdisciplinary work is a particularly important factor when approaching sport science from a problem-based perspective (Güllich & Krüger, 2022). Specifically, we argue that interdisciplinarity becomes crucial when we are trying to develop solutions for complex challenges in sport, the health sector, and society in general. For example, an interdisciplinary approach in sport science might merge aspects of psychology, physiology, and sociology with expertise of medical professionals to study and realize health promotion strategies. For the purpose of this editorial, we understand interdisciplinarity as a collaboration between individuals from different scientific disciplines but also from different professions with the goal of combining knowledge and methods to create new solutions for complex societal problems. This can range from the simple communication of ideas and experiences to mutual integration of concepts, methodologies, procedures, or data sharing (Zaiț et al., 2021). We think that sport scientists can and should take a leading role in such collaborations given their unique cross-disciplinary education related to human health, performance, and well-being. Leadership in interdisciplinary collaborations may be an opportunity for us as sport scientists to strengthen our profile and image in the society and to take responsibility in addressing societal challenges (Hottenrott et al., 2017). In preparation of this year's ÖSG Congress in Innsbruck 2024, we tried to embrace this idea of interdisciplinarity in sport science. Before the event, we conducted an online survey across the DACH region (Germany, Austria, Switzerland) to identify current societal challenges that sport science should address and help with developing solutions. In parallel, we assessed the perceived importance of interdisciplinary work among sport scientists and related professions. Potential respondents to the survey were mainly contacted through the communication channels of the ÖSG and its equivalent associations in Germany (dvs) and Switzerland (SGS). Consequently, respondents included sport scientists as well as professionals from other fields who follow or are part of the activities of sport science associations. The findings of the survey were used in three different ways and will be described in this editorial: • to summarize the most frequently mentioned challenges and topics that sport science should address and help with developing solutions, • to develop an "Interdisciplinary Innovation Workshop" for the ÖSG Congress in Innsbruck 2024 where delegates transform the identified challenges into specific problems that can be solved, and • to compare the survey results with the content of the scientific abstracts submitted to the ÖSG Congress in Innsbruck 2024 and determine the alignment between the identified challenges and current research topics within the ÖSG community. The survey - Current challenges for sport science and beyond The survey responses were analyzed in MAXQDA 24 (VERBI software, 2021). The MAXQDA AI-Assist tool was used to suggest an initial coding scheme to group responses into categories. Two researchers refined the scheme into a final code set, independently coded the participants' responses, and discussed mismatches to agree on the final code assignments. The survey yielded 176 responses, of which 85 were fully completed. Respondents (42% women) had a mean age of 40.2 years (± 13.8). Regarding their primary professional field, 34% identified as scientists working at a university, college, or research institution, 26% were healthcare professionals (e.g., physicians or therapists), 15% worked in the private sector including self-employment, 13% were students or educators, and 12% were either coaches, athletes, or employed within a sports federation. 91% reported that interdisciplinarity was a key component of their work. The most frequently mentioned challenges fell into the category of "prevention and rehabilitation" (34%), followed by "job profiles related to sport science and exercise therapy" (23%), "sport science mission for research and education" (11%), "broader societal issues" (5%), "structural development of organized and non-organized sports" (5%), "inclusion and integration through sports" (4%), "self-awareness and self-reflection" (3%), "technological progress" (2%), "financing" (2%), and "elite sports" (2%; orange bars in Figure 1). Coding was not possible for 5% of the answers. The workshop - Transforming challenges into specific problems Building on the findings of the survey, we collaborated with the ikivox collective (Nyon, France, https://ikivox.org/en/) to develop an "Interdisciplinary Innovation Workshop" held at the ÖSG Congress in Innsbruck 2024. With the help of ikivox who specialize in collective intelligence and collaborative design approaches, we designed a workshop with the following objectives: • to transform the identified challenges into specific problems that can be solved with innovative solutions • to experience interdisciplinary collaboration and new ways of working together • to position the Austrian Sport Science Society (ÖSG) as an enabler, bringing value to its members to improve exchange about sport science in Austria • to identify whether the teamwork could continue on some topics after the Congress with the support of the ÖSG Eventually, 42 Congress delegates signed up for the workshop and could choose to work on one of the following challenges: "physical inactivity at the work place", "physical inactivity in children", "image of sport science in society", "role of exercise therapists in medical teams", "influence of menstrual cycle on athletic performance", "health awareness in society", "inclusion of bodily disabled individuals as participants in public sport events", and "integration of girls and women with migration background through sports". This format of collaboration may provide a framework for future interdisciplinary initiatives within the ÖSG and beyond. The Congress abstracts - Comparing the identified challenges with actual research topics at the ÖSG Congress Having identified current challenges for sport science, it seemed of interest to compare those challenges with the content of the submitted scientific contributions to the ÖSG Congress in Innsbruck 2024. The Congress received 78 contributions including 60 regular abstracts, 12 Young Investigator Award submissions and 6 extended abstracts. Five section editors managed the peer-review process and drew on the expertise of 45 peer reviewers. Each contribution was evaluated and rated by two independent reviewers. Critical feedback of reviewers had to be addressed by the authors in revised abstract submissions. Following the revision round, 75 contributions were accepted for presentation at the Congress. The contributions spanned a wide range of research areas including "biomechanics, motor control & sports technology" (26% of abstracts), "sport psychology & pedagogy" (25%), "sports medicine, exercise therapy & public health" (20%), "sports physiology & exercise science" (16%), "sports sociology, economy & management" (14%). Of all contributions, 64 were presented orally and 11 as poster presentations while 65 abstracts were published in the Congress proceedings.